Comparative Analysis of Selenium and Quercetin Nanoparticles for their Antioxidant and Hepatoprotective Effects Against Acrylamide-Induced Liver Toxicity in Male Albino Wistar Rats - Faridi, Uzma; Al-Awthan, Yahya; Sakran , Mohamed; Zidan, Nahla; Al-Mutairi, Fahad; Quseen Akhtar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Acrylamide, a potential occupational carcinogen, is a natural by-product formed during the thermal processing of starchy foods and roasted coffee beans. Recent studies have also reported high levels of acrylamide in various thermally treated fast foods in Saudi Arabia. This study aims to meet the critical need for effective antioxidant therapies to mitigate acrylamide-induced liver damage. By comparing the protective effects of selenium and quercetin nanoparticles, it seeks to identify the more potent nano-antioxidant, thereby contributing to the advancement of safer and more efficient strategies for preventing chemically induced hepatotoxicity. Twenty adult male Albino Wistar rats were randomly divided into four groups: control, acrylamide-treated, acrylamide + SeNP, and acrylamide + QNP. Acrylamide exposure (Acrylamide exposure (50 mg/kg/day, orally for 21 days)) significantly elevated serum levels of cholesterol (CHO), triglycerides (TG), low-density lipoprotein (LDL), alanine transaminase (ALT), aspartate transaminase (AST), creatinine, and urea, cholesterol (233.33 ± 7.50 mg/dL), (238.33 ± 4.93 mg/dL), (67.33 ± 2.51 mg/dL), (80.33 ± 3.51 U/L), and AST (80.00 ± 3.00 U/L) respectively, compared to the control group (CHO: 155.33 ± 8.02, TG: 150.00 ± 7.93, LDL: 39.33 ± 4.16, ALT: 16.66 ± 3.78, AST: 22.66 ± 2.08). while significantly reducing glutathione (GSH) and superoxide dismutase (SOD) levels in liver tissues compared to the control group. Treatment with SeNPs and QNPs led to a marked reduction in these altered biochemical parameters and improved liver histopathology. In conclusion, selenium and quercetin nanoparticles exhibited a protective effect against acrylamide-induced hepatotoxicity in male Albino Wistar rats, suggesting their potential use in mitigating liver damage caused by environmental toxins.